Institutional Knowledge Management Systems and Faculty Performance in Management Education - Ashun Malik; Dr. Shinki Katyayani Pandey (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Knowledge management (KM) systems have become increasingly critical for educational institutions seeking to enhance organisational effectiveness and academic excellence. This study investigates the relationship between institutional knowledge management systems and faculty performance in management education institutions. Through a quantitative research design, data were collected from 156 faculty members across five management institutions in Rohtak, Haryana, using a structured questionnaire that measured the effectiveness of the KM system across four dimensions: knowledge acquisition, knowledge storage and retrieval, knowledge dissemination, and knowledge application.